Mapping Trends in Air Quality Research in South Africa: A Bibliometric Analysis, 1998-2024 - Sekwatlakwatla, Sello Prince; Malele, Vusi; Toona, Priscilla; Tshilongo, James; Mkhohlakali, Andile; Letsoalo, Refiloe; Mabowa, Happy; Ntsasa, Napo (Journal of Information System and Informatics, 2025)
The foundation of South Africa is the Constitution, which guarantees every citizen access to a safe and healthy environment. Despite a wealth of research on lower-income households, the effects of burning wood for cooking, heating, and comfort in South African homes are also affecting the air quality; even if the government is working very hard to put measures in place to improve air quality, it will be very difficult to accommodate every household in South Africa. South Africa's low-income urban settlements focus on air quality monitoring for policy formulation and strategy building and Lack of garbage removal services and systems is another characteristic of low-income communities that exacerbates ambient air pollution levels. Based on the quantity of South African publications and citations in air quality that are listed in the Scopus and Web of Science databases, the study used bibliometric analysis to look at the country's air quality and the factors that affect it. Data was collected from 1998 to 2024; the results show that air pollution, nitrogen dioxide and emissions are causing a risk to children, and also having a high impact in causing diseases like asthma, respiratory health and climate change is playing a critical role in increasing the risk. Moreover, the word cloud reflects a growing emphasis on certain air pollutants, including NO₂, PM2.5, black carbon, and SO₂. NO₂ has been linked to substantial health implications, including respiratory disorders, asthma aggravation, and cardiovascular issues.